2013
DOI: 10.1002/jobm.201300528
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of antagonistic‐potential of two Bacillus strains and their biocontrol activity against Rhizoctonia solani in tomato

Abstract: To investigate the biocontrol mechanism of two antagonistic Bacillus strains (Bacillus subtilis MB14 and Bacillus amyloliquefaciens MB101), three in vitro antagonism assays were screened and the results were concluded that both strains inhibited Rhizoctonia solani growth in a similar manner by dual culture assay, but the maximum percent of inhibition only resulted with MB101 by volatile and diffusible metabolite assays. Moreover, cell free supernatant (CFS) of MB101 also showed significant (p > 0.05) growth in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 27 publications
4
10
0
Order By: Relevance
“…In contrast, we observed an increase in relative area dedicated to thylakoid structures in chloroplasts within PA23-treated plants coupled with an increase in total chlorophyll content and repression of CLH1. In other studies, BCA application has been associated with increased chlorophyll in the plant host [6062]. The lack of overexpression of CLH1 in the PA23-only treatment group is consistent with evidence showing that CLH1 is only induced after cellular collapse, a defense response not elicited by nonpathogenic organisms [63].…”
Section: Discussionsupporting
confidence: 86%
“…In contrast, we observed an increase in relative area dedicated to thylakoid structures in chloroplasts within PA23-treated plants coupled with an increase in total chlorophyll content and repression of CLH1. In other studies, BCA application has been associated with increased chlorophyll in the plant host [6062]. The lack of overexpression of CLH1 in the PA23-only treatment group is consistent with evidence showing that CLH1 is only induced after cellular collapse, a defense response not elicited by nonpathogenic organisms [63].…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, the most promising bacterial isolates harbor at least two of lipopeptide genes in the genome, as revealed by PCR investigation. This agrees with several authors [9,11,[53][54][55] who described the presence of multiple LP-genes in Bacillus strains exhibiting antagonistic activity. The antifungal properties of lipopeptides have been deeply investigated.…”
Section: Discussionsupporting
confidence: 93%
“…More specifically, PO is involved in the synthesis and modulation of reactive oxygen species (ROS), which could act directly or indirectly to restrict pathogen viability and expansion (Shoresh et al 2010). Similar observations of higher PO and PPO activity in tomato plants fortified with Bacillus amyloliquefaciens MB101 in the presence of R. solani were noticed by Solanki et al (2015). The results of present study indicated that H. lixii and T. asperellum-treated tomato plants develop tolerance toward root rot infections by triggering enzymatic activities of PO, PPO, PAL, and TPC.…”
Section: Discussionmentioning
confidence: 56%